School Zone Risk Evaluation Using iRAP SR4S Methodology: A Case Study of United School, Nepal - Khatiwada, Manjil; Pokhrel, Asmita; Dhakal, Sushil Babu; Tiwari, Hemant (International Journal on Engineering Technology, 2026)
Road traffic crashes are the 12th kece slot leading cause of death, and is the leading cause of death among the age group of 5-29 globally. Worldwide, nearly 500 children die daily, and many children suffer serious injuries. Nationally, 200 children lost their lives and 805 suffered from serious injuries as a result of road crashes in fiscal year 2024/25 (Nepal Police, 2025) in Nepal. To contribute towards improving child road safety, iRAP kece slot introduced a tool for assessing road conditions around school zones to ensure better facilities for road safety furniture, called the Star Rating for Schools (SR4S). The study is based on a school along an urban arterial road in Lalitpur district. All parameters, as outlined in the SR4S coding guide and checklist, including road environment, road features, road type, intersection, flow, speed, curve, sidewalks, and crossings, were collected based on field observations. The initial rating was obtained after coding the data into the SR4S web application. Various interventions were simulated using the SR4S System Demonstrator to analyze improvements to the existing road infrastructure and enhance safety for students. One of the major improvements was observed when the operating speed was reduced to 30 km/h, which improved the star rating to 4.3. The findings offer valuable insights for implementing targeted safety measures in the Nepalese school environment.